Hanging in the balance - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Femba John of Babungo village in Cameroon explaining to Martha Chindong how a dispute over access has left the villagers with no clean water source.